Effect of accelerated solvent extraction conditions on the isolation of bioactive compounds from fennel (Foeniculum vulgare Mill.) seeds - Repajić, Maja (Array, 2020)
This study focused to establish the optimal conditions of accelerated solvent extraction (ASE), i.e., temperature, static extraction time and number of extraction cycles, for the isolation of fennel (Foeniculum vulgare Mill.) seeds phenols and pigments using 96% ethanol as an extraction solvent. Hence, extraction conditions of temperature (80 and 110 °C), static extraction time (5 and 10 min) and number of extraction cycle (1, 2, 3 and 4) were varied. Obtained extracts were spectrophotometrically analyzed for the content of total phenols (TP), total chlorophylls (TCHL) and total carotenoids (TCAR). Applied extraction conditions had a significant (p<0.01) influence on the yields of analyzed compounds, except for static extraction time on TCAR (p=0.11). Based on the results of statistical analysis, the highest levels of TP and TCHL were achieved at the most invasive conditions (110 °C/10 min/4 cycles), while shorter period was sufficient to reach the highest TCAR yield (110 °C/5 min/3 cycles). In summary, ASE demonstrated to be effective extraction technique for the isolation of fennel seeds hydrophilic and lipophilic bioactive compounds.